Penelitian Pembuatan Bahan Aktif Pestisida Dari Sumber Hayati - Emmy Ratnawati (Balai Besar Kimia dan Kemasan, 1985)
Natural pesticide resources that ever been developed in Indonesia are Tobacco (Nicotiana Tabacum L) contains 2-5% nicotine in leaf, 0,47- 0,87 nicotine in stem, Derris Eliptica contains 1- 14% rotenone. Phyrethrum (Phyrethrum Cineraefolium) contains 1-1,5% pyrethrin, Phachyrrhizus Erosus Urban contains 1-5,5% pachyrrhizid and Black Pepper (Piper Nigrum L) contains piperine. Tobacco and Black Pepper are the potential resources that can be developed as natural pesticides because it have better availibility.